THE EFFECT OF AUDIT QUALITY, AUDIT COMMITTEE, AND AUDIT TENURE ON FRAUD IN FINANCIAL REPORTS: (Empirical Study of Healthcare Manufacturing Companies Listed on the Indonesia Stock Exchange 2019–2023) - Nurhasanah; Emi Masyitah; Ina Liswanty (International Journal of Management, Economic and Accounting, 2025)
This study is motivated by the increasing cases of financial statement fraud in the Indonesian healthcare sector, such as PT Indofarma Tbk and PT Kimia Farma Tbk, which caused significant losses Based on the Fraud Triangle theory, fraud occurs due to pressure, opportunity, and rationalization. This research aims to analyze the effect of audit quality, audit committee, and audit tenure on financial statement fraud in healthcare manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2019-2023. The research employed a quantitative approach with an associative method Secondary data from annual financial reports were analyzed using multiple linear regression after passing classical assumption tests. The results show that audit quality, audit committee, and audit tenure partially have no significant effect on financial statement fraud . However, simultaneously, the three variables have an influence, although not significant, on financial statement fraud . These findings indicate that preventing fraud does not rely solely on these internal factors but requires more comprehensive supervision and the implementation of good corporate governance